CHARACTERISTICS OF DEVELOPING MORAL EDUCATION IN CHILDREN - Urozov Fakhriddin Isakovich (Scholar Express Journal, 2022)
He considers spiritual and moral education to be an important factor in raising the young generation to become a mature person. The necessity of spiritual and moral education of these children, as well as its specific features, will be considered
Keywords: Morality; education; young children; modesty